Education of the 5M Movement and Balanced Nutrition in the Face-to-Face Learning Period for Muhammadiyah High School Students 18 - Haris Muzakir; Muhammad Furqon; Alib Birwin (ABDIMAYUDA: Indonesia Journal of Community Empowerment for Health, 2022)
The current Covid-19 pandemic has caused several sectors to experience difficulties in carrying out their activities. This also occurs in the education sector, where educators and students are limited in carrying out the learning process directly in the classroom. The risk of spreading can occur during face-to-face learning. PKM activities are carried out by providing counseling to tenth grade students of SMA Muhammadiyah 18 Jakarta regarding how to use masks, washing hands, maintaining distance, avoiding crowds and limiting mobility (5M) and balanced nutrition among students. Before counseling on the 5M program and balanced nutrition, tenth grade students of SMA Muhammadiyah 18 Jakarta did a pre-test. The pre-test was conducted to determine the students' initial knowledge about the 5M program and balanced nutrition. As a form of evaluation of PKM activities, a post-test was also conducted to determine the increase in knowledge from the material presented. The post-test results showed that participants experienced a good increase in knowledge, regarding social distancing by 70%, wearing masks by 74%, washing hands 84%, avoiding crowds by 89%, limiting mobility by 67% and balanced nutrition by 5%. The expected implication after holding this outreach is the students can implement measures to prevent the transmission of Covid-19, so that Covid-19 cases, especially among students, can be suppressed.